Utopian community football? Sport, hope and belongingness in the lives of refugees and asylum seekers. Issue 2 (4th March 2018) - Stone, Chris
Abstract: Refugees and asylum seekers have become increasingly demonised as part of anti-migrant sentiment leading to social exclusion. Sport has been utilised as a tool for social cohesion though evidence as to its efficacy in such a task is limited. Based on a three-year research programme exploring the role of football in the lives of refugees and asylum seekers in the U.K., this paper examines the concept of belonging, provides evidence for the role of community-based sport in social development and concludes with a call for practitioners to maximise their belief in concrete utopian ideals without losing the inherent critical approach needed to positively develop the industry in which they work.